Construct Validity of a Serious Game for Laparoscopic Skills Training: Validation Study - IJgosse, Wouter; van Goor, Harry; Rosman, Camiel; Luursema, Jan-Maarten (JMIR Publications, 2020)
BackgroundSurgical residents underutilize opportunities for traditional laparoscopic simulation training. Serious gaming may increase residents' motivation to practice laparoscopic skills. However, little is known about the effectiveness of serious gaming for laparoscopic skills training. ObjectiveThe aim of this study was to establish construct validity for the laparoscopic serious game Underground. MethodsAll study participants completed 2 levels of Underground. Performance for 2 novel variables (time and error) was compared between novices (n=65, prior experience <10 laparoscopic procedures), intermediates (n=26, prior experience 10-100 laparoscopic procedures), and experts (n=20, prior experience >100 laparoscopic procedures) using analysis of covariance. We corrected for gender and video game experience. ResultsControlling for gender and video game experience, the effects of prior laparoscopic experience on the time variable differed significantly (F2,106=4.77, P=.01). Both experts and intermediates outperformed novices in terms of task completion speed; experts did not outperform intermediates. A similar trend was seen for the rate of gameplay errors. Both gender (F1,106=14.42, P<.001 in favor of men) and prior video game experience (F1,106=5.20, P=.03 in favor of experienced gamers) modulated the time variable. ConclusionsWe established construct validity for the laparoscopic serious game Underground. Serious gaming may aid laparoscopic skills development. Previous gaming experience and gender also influenced Underground performance. The in-game performance metrics were not suitable for statistical evaluation. To unlock the full potential of serious gaming for training, a more formal approach to performance metric development is needed.